Financial and economic support of innovation activity - Shchebetova, A. O.; Pererva, P. G. (WSEH, 2024)
The report proves that the effectiveness of all financial and economic measures is most often assessed by the size of the economic efficiency of innovations and innovation activities: the economic effect of the introduction of innovations (reduction of costs, increase in income) is determined; Forecasting models are used to estimate the long-term benefits of innovation
Фінансово-економічне забезпечення інноваційної діяльності
Keywords: financial measures; innovation activities; efficiency; technologies; development models